Writing, Graphic Codes, and Asynchronous Communication. (10th October 2018) - Morin, Olivier; Kelly, Piers; Winters, James
Abstract: We present a theoretical framework bearing on the evolution of written communication. We analyze writing as a special kind of graphic code. Like languages, graphic codes consist of stable, conventional mappings between symbols and meanings, but (unlike spoken or signed languages) their symbols consist of enduring images. This gives them the unique capacity to transmit information in one go across time and space. Yet this capacity usually remains quite unexploited, because most graphic codes are insufficiently informative. They may only be used for mnemonic purposes or as props for oral communication in real‐time encounters. Writing systems, unlike other graphic codes, work by encoding a natural language. This allows them to support asynchronous communication in a more powerful and versatile way than any other graphic code. Yet, writing systems will not automatically unlock the capacity to communicate asynchronously. We argue that this capacity is a rarity in non‐literate societies, and not so frequent even in literate ones. Asynchronous communication is intrinsically inefficient because asynchrony constrains the amount of information that the interlocutors share and limits possibilities for repair. This would explain why synchronous, face‐to‐face communication always fosters the development of sophisticated codes (natural languages), but similar codes for asynchronous communication evolve with more difficulties. It also implies that writing cannot have evolved, at first, for supporting asynchronous communication. Abstract : Writing is the only type of graphic codes that enables the transmission of knowledge across space and time, which makes it a powerful tool for boosting cumulative culture. Based on a typology of graphic codes, Morin, Kelly, and Winters analyze the properties that endow writing with the potential to encode novel information in a productive way, and they show why the invention of writing is necessary, but not sufficient, for achieving asynchronous communication.